FACTORS AFFECTING PREGNANT WOMEN IN CONSUMPTING FE TABLETS IN PAYA PEUNAGA VILLAGE MEREUBO DISTRICT, WEST ACEH DISTRICT - Maya Sari; Khairunnas; Itza Mulyani; Wardah Iskandar (RADJA PUBLIKA, 2024)
Iron is one of the important minerals needed during pregnancy. Pregnant women who do not comply with taking Fe tablets may have the potential for anemia. This research aims to determine the factors that influence the compliance of pregnant women in consuming Fe tablets in Paya Peunaga Village, Meureubo District, West Aceh Regency. The type of research used is an analytical survey with quantitative methods, cross sectional design. The population of all pregnant women in this study was 71 people with a total sampling of 71 people. Data collection uses primary data by distributing questionnaires. The research results showed that there was no effect of age on the consumption of Fe tablets in pregnant women, p-value 0.307>α (0.05). There is an influence of education on the consumption of Fe tablets in pregnant women p-value 0.037<α (0.05). There is an influence of work on the consumption of Fe tablets in pregnant women p-value 0.023<α (0.05). There is an influence of knowledge on the consumption of Fe tablets in pregnant women p-value 0.002<α (0.05). There is no effect of parity on consumption of Fe tablets in pregnant women p-value 0.115> α (0.05). Maternal knowledge is the dominant factor influencing consumption of Fe tablets in pregnant women (p=0.012, OR=2.905). It is hoped that it can increase pregnant women's knowledge about the importance of consuming Fe tablets regularly so as to reduce the prevalence of anemia.